Neuronal Representations of Tactic-Based Sensorimotor Transformations in the Primate Medial Prefrontal, Presupplementary, and Supplementary Motor Areas: A Comparative Study - Awan, Muhammad Ali Haider; Mushiake, Hajime; Matsuzaka, Yoshiya (Frontiers in Systems Neuroscience, 2020)
Flexible context-dependent behaviors necessitate flexible selection of multiple behavioral tactics, i.e., internal protocols for selecting an action. Previous primate studies have shown that the posterior medial prefrontal cortex (pmPFC) contributes to the selection, retention, and use of tactics, but the manner in which this area employs selected tactics to convert sensory information into action and how that manner differs from downstream cortical motor areas have yet to be fully elucidated. To address this issue, the present study recorded neuronal activity in two monkeys as they performed a two-choice arm reaching task that required the selection of multiple tactics when converting spatial cue information into the direction of arm reaching. Neurons in the pmPFC exhibited selective activity for tactics during their selection, their maintenance in memory, and their use in determining an action. Additionally, many individual pmPFC neurons exhibited selective activity for tactics, cue location, action, or a combination of these variables in the behavioral epoch in which the action was determined. At the population level, pmPFC neurons represented tactics, cue location, and the resultant action. In the adjacent presupplementary motor area (pre-SMA), neuronal populations represented both tactics and action, whereas the neurons in the SMA mainly represented the action. Taken together, the present results indicate that, of these three areas, the pmPFC plays a cardinal role during the integration of behavioral tactics and visuospatial information when selecting an action.